Domestic pressure and international climate cooperation - Alessandro Tavoni; Ralph Winkler (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2020)
In the wake of 25 UN Climate Change Conferences of the Parties (and counting), international cooperation on mitigating greenhouse gas emissions to avoid substantial and potentially irreversible climate change remains an important challenge. The limited impact that the Kyoto Protocol and its successor, the Paris Agreement, have had on curbing emissions demonstrate both the dificulties in negotiating ambitious environmental agreements and the reluctance of countries to comply with their agreed emission targets once they have joined the treaty. Therefore, a better understanding of the obstacles and opportunities that the interactions between domestic and international policy pose for the design of successful international climate cooperation is of utmost importance. To shed light on the roots of the stalemate (and suggest possible ways out), this article reviews, and draws lessons from, a growing theoretical, experimental and empirical literature that accounts for the hierarchical interplay between domestic political pressure and international climate policy.
Keywords: 330; international climate cooperation; hierarchical policy-making; domestic pressure; special interest groups; (strategic) delegation